VD_FINDINFO Arrêt / 2025 / 374 vom 11. Juni 2025 - VD Tribunal cantonal (2025)
NOUVELLE DEMANDE, RENTE D'INVALIDITÉ, DROIT D'ÊTRE ENTENDU, PRÉAVISASSURANCE SOCIALE | 29 al. 2 Cst., 57a al. 1 LAI, 42 LPGA, 49 al. 3 LPGA, 87 RAI